Neonatal outcomes of birth asphyxia in tertiary care hospital of low-income country (Journal of Fatima Jinnah Medical University, 2021)
Background: Pakistan has highest neonatal mortality in the region and birth asphyxia is one of the main preventable contributors to this. Objective of this study is to determine the frequency of different neonatal outcomes in neonates with birth asphyxia.Subjects & Methods: It was descriptive case series study conducted in Department of Pediatrics Medicine, Services Hospital, Lahore in 6 months period during 6th Dec 2016 to 5th June 2017. 150 cases were included using non probability, consecutive sampling with 95% confidence level, 6% margin of error taking an expected percentage of neonate mortality as 15%. Data was analyzed with SPSS version 23. Categorical variables i.e., gender and neonatal outcomes in terms of neonatal mortality, discharge and neurological complications were expressed by frequency and percentage. Post stratification chi square test was applied. A p-value of
Keywords: Neonates; Birth Asphyxia; Mortality; Neurological complications; Low-income country